2004
DOI: 10.1007/s00134-004-2470-7
|View full text |Cite
|
Sign up to set email alerts
|

The neuroendocrine stress response and severity of acute respiratory syncytial virus bronchiolitis in infancy

Abstract: Whereas the effect of intensive care (mechanical ventilation and medication) could not be controlled for, our results suggest that there is an association between the neuroendocrine hormone response, severity of illness and degree of lymphopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 18 publications
2
36
0
Order By: Relevance
“…The high incidence of hyperglycemia (99%) in our study is similar to the incidence of hyperglycemia reported in children requiring MV and vasoactive infusion (93%) (9). Insulin resistance associated with counter-regulatory hormonal response is believed to be the mechanism involved in hyperglycemia in both settings (5,9). In RSV infection, the association between severity of illness and counter-regulatory response (5) could explain the association we now report between hyperglycemia and prolonged duration of MV and length of PICU stay.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The high incidence of hyperglycemia (99%) in our study is similar to the incidence of hyperglycemia reported in children requiring MV and vasoactive infusion (93%) (9). Insulin resistance associated with counter-regulatory hormonal response is believed to be the mechanism involved in hyperglycemia in both settings (5,9). In RSV infection, the association between severity of illness and counter-regulatory response (5) could explain the association we now report between hyperglycemia and prolonged duration of MV and length of PICU stay.…”
Section: Discussionsupporting
confidence: 89%
“…[11-13.9] cm H 2 O, p ϭ .06). PEEP at admission was also similar between peak sustained glucose bands, and peak PEEP was higher in the HG group (6 [6 -7.5] vs. 5 [5][6] cm H 2 O) ( Table 1).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Our study confirmed the results of TASKER et al [30] who showed, in serum, that during the acute phase of RSV LRTI, infants requiring mechanical ventilation have higher growth hormone levels in plasma compared with hospitalised, nonventilated infants. This higher level of growth hormone in plasma can explain the higher level found in NPAs in this study.…”
Section: +supporting
confidence: 92%
“…Other manifestations includes raised antidiuretic hormones; ADH (Hanna et al, 2003), prolactin and leptin inbalance (Tasker et al, 2004), association with hepatitis (Griffin et al, 1979), hypothermia (Njoku and Kliegman, 1993), exenthems, thrombocytopenia and conjunctivitis (Fujishima et al, 1995).…”
Section: Seizuresmentioning
confidence: 99%